Assessing the Impact of Non-Interest Banking on Financial Inclusion: A Study of Selected States in Nigeria - Okoh, Johnson Ifeanyi; Adam, Sa'adatu Balarabe; Abdurrahaman, Daha Tijjani; Ozigbo, Ada Mac - (NIU Journal of Social Sciences, 2024)
This paper investigated the transformative potential of non-interest banking on financial inclusion within selected Nigerian states. Non-interest banking, grounded in Islamic principles, has garnered substantial scholarly attention across Muslim-majority nations. However, its nuanced effects on financial inclusion in Nigeria necessitated comprehensive examination. This study sought to address this gap by scrutinizing the intricate dynamics and discerning whether non-interest banking engenders heightened financial inclusion and socio-economic advancement. Interrogating the linkages between accessibility of non-interest banking services, individuals' attitudes toward non-interest banking, customer satisfaction, government support, trustworthiness of non-interest banks, and their collective impact on financial inclusion constitutes the focal point of inquiry. The study adopted a quantitative research paradigm, employing purposive random sampling to solicit responses from 380 participants encompassing Nigeria's diverse geopolitical zones. A tailored questionnaire, informed by extant scholarship, was meticulously administered, with data analysis done using Structural Equation Modeling (SEM) facilitated by SmartPLS v3.2.7. The findings underscored that customer satisfaction, perceived government support, and trustworthiness of non-interest banks significantly and positively influence financial inclusion. Nevertheless, the nexus between accessibility of non-interest banking services and attitudes toward non-interest banking with financial inclusion did not attain statistical significance within this model. The research attains an R2 value of 0.704 for financial inclusion, signifying an explanatory capacity of 70.4%. This research extended valuable insights for policy formulation and decision-making, by accentuating the pivotal role of customer-centric strategies, governmental endorsement, and credibility in amplifying financial inclusion through non-interest banking channels. Keywords: Non-interest banking, financial inclusion, Nigeria, Structural Equation Modeling